Effect of Plant Spacings and Seed Germination Methods on Performance of Spring Rice (Oryza Sativa L. cv. Hardinath-1) under the System of Rice Intensification (SRI) - Dhakal , Suraj; Gauli, Bibek; G.C., Samser (Agronomy Journal of Nepal, 2025)
Rice (Oryza sativa L.) is a major staple crop in Nepal. This study evaluated the effects of plant spacing and germination methods on the performance of spring rice (Hardinath-1) planted under System of Rice Intensification (SRI) in Gauradaha, Jhapa, Nepal, in 2022. The seed germination methods (pre-germinated, Ps, vs. normal, Ns) and plant spacings (20 cm × 20 cm, 30 cm × 30 cm, 40 cm × 40 cm) were used as treatments. The experiment was conducted using a randomized complete block design (RCBD) with six treatment combinations and four replications, assessing major agronomic traits and yield attributes. The study involves nursery and field preparation, transplanting 16 days old seedlings, fertilizer management, and intercultural operations, following SRI guidelines. Results revealed that the pre-germinated seeds (Ps) initially produced taller plants compared to normal seeds (Ns), but had no significant impact on any parameter from either type. The 20 cm × 20 cm spacing showed the highest grain yield (4.29 mt/ha) due to higher planting density, despite fewer tillers per plant and inferior growth performance compared to wider spacings. The spacings of 30 cm × 30 cm and 40 cm × 40 cm enhanced individual plant performance with lesser yield attributes (3.48 mt/ha and 3.10 mt/ha) due to the wasted area. Grain moisture and thousand-grain weight also showed no significant differences across all treatments. The findings recommend 20 cm × 20 cm spacing under SRI to maximize spring rice productivity in Jhapa, accentuating efficient use of resources and sustainable practices.